(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
in the article, some comments on the concepts of economic consciousness, economic thinking, economic activity, two main directions of raising economic consciousness and economic thinking to the level of modern requirements, economic literacy is based on the fact that we are all consumers of delicacies - we all need it like water. Also, it has been proven that the cooperation of the state and the general public in accelerating the pace of economic development, the role of education in the development of economic consciousness and economic thinking, the possibilities of developing economic thinking are limitless, only its effective use is an acute necessity.